2015
DOI: 10.1016/j.eatbeh.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Media internalization and conformity to traditional masculine norms in relation to body image concerns among men

Abstract: Previous studies have separately examined conformity to masculine norms and internalization of body ideals in the media in relation to the drive for muscularity (DM). This study was designed to examine these factors together in relation to DM, and further examine how they may differ in relation to drive for thinness (DT) and drive for leanness (DL).Participants were 284 Australian males between ages 18 to 42. They completed validated measures that assessed DM, DT, DL, male gender role norms, and internalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 48 publications
1
32
0
2
Order By: Relevance
“…It is known that the mass-media exposure with body image ideals affects men and women and gives rise to body image concerns. 59,60 In this review, there was a trend in the majority of the studies to report on young women with body image concerns rather than men; however, some studies also showed body image concerns among men. This implies that the focus should not only be women with an ICD, but that men also have body image concerns, although the extent of concerns in both genders needs to be further established.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is known that the mass-media exposure with body image ideals affects men and women and gives rise to body image concerns. 59,60 In this review, there was a trend in the majority of the studies to report on young women with body image concerns rather than men; however, some studies also showed body image concerns among men. This implies that the focus should not only be women with an ICD, but that men also have body image concerns, although the extent of concerns in both genders needs to be further established.…”
Section: Discussionmentioning
confidence: 93%
“…It is known that the mass‐media exposure with body image ideals affects men and women and gives rise to body image concerns . In this review, there was a trend in the majority of the studies to report on young women with body image concerns rather than men; however, some studies also showed body image concerns among men.…”
Section: Discussionmentioning
confidence: 99%
“…A young man's desire to have the perfect masculine body is fuelled by the proliferation of the mesomorphic body shape in the media (Daniel and Bridges 2010). Moreover, internalisation of body ideals mediated the relationship between masculine role norms and body image in the drive for muscularity (De Jesus et al 2015) and body image concern is a risk factor for AAS use (Kanayama et al 2006;Jenssen and Johannessen 2015). Arguably, this body ideal is not just targeted at young men, increasingly media representations of middle-age celebrities focus on a muscular physique, and the 2015 UK survey on IPEDs found that a number of participants started use after the age of 40 (Bates and McVeigh 2016).…”
Section: Risks To the Initiation Of Aas Usementioning
confidence: 99%
“…Needless to say when I saw her 2 years later her jaw dropped, brushing her off at that moment was probably the best feeling I have experienced in my life [text in Zyzz transformation progress video] (Underwood 2017) Or, Jon Skywalker, who self-promotes his change in physical appearance from AAS use and has a personal motto of 'lifes too short to be unaesthetic (sic)' (Skywalker 2017). Studies have shown that men choose an ideal body that is more muscular than themselves and estimate that women prefer a more muscular male body (Pope et al 2000) and the media does influence the drive for muscularity (Cramblitt and Pritchard 2013;De Jesus et al 2015;Melki et al 2015). Retailers and the media promote various ideal body images whilst taking no responsibility for the negative impact they have on their audience.…”
Section: Risks To the Initiation Of Aas Usementioning
confidence: 99%
“…Limitations of previous studies include the focus on quantitative clinical presentation in male patients with eating disorders [ 4 ], as well as that on non-clinical samples [ 14 , 15 ]. Moreover, even though the number of reported eating disorders cases has been increasing in Asia, available data is still lacking [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%